Assessing The Effectiveness Of Differentiated Instruction In Reading Skills Learning: Its Impact On Student Motivation - Nurhidayati, Nurhidayati; Mardatillah, Harrifah; Furqon, Muhammad Rizalur (IAIN Bone, 2025)
This research is motivated by heterogeneous class conditions, especially in Arabic language learning, where students' abilities significantly differ. This difference is especially seen between students with a background in Islamic boarding school education and those without, thus requiring a learning approach responsive to this diversity. This study aims to examine the effectiveness of differentiated learning in Arabic language learning, especially reading skills, and to analyze its impact on students' intrinsic and extrinsic motivation. The method used is quantitative research with a pre-experimental one-group pretest post-test type design. The subjects of this study were 24 students of class XI IPS who had followed the differentiated learning process. The main instrument was a motivation questionnaire compiled based on Gardner and Lambert's theory and observations during the learning process. Differentiated learning was implemented by dividing students into three groups (superior, medium, and low) based on the initial diagnostic assessment. Adjustments were made to the context of the reading text and trigger questions as an implementation of the process differentiation. The data analysis showed a significant difference between the pretest and post- test scores of students' learning motivation, as evidenced by the Paired Samples t-test with a significance value of 0.000 (p < 0.05). This finding indicates that the application of differentiated learning effectively increases students' learning motivation and improves Arabic reading skills. These findings confirm that adaptive and student-centered learning strategies are essential to creating meaningful learning experiences. Differentiated learning is effective in increasing students' learning motivation. With this approach, students become more active in asking questions without feeling inferior to their smarter friends. They also show higher persistence in completing assignments despite facing challenges because the level of difficulty of the material is adjusted to their respective abilities. In addition, differentiated learning also contributes significantly to strengthening students' reading skills.